First report and molecular prevalence of potential zoonotic Enterocytozoon bieneusi in Turkish tumbler pigeons (Columba livia domestica). (16th March 2021) - Pekmezci, Didem; Yetismis, Gamze; Colak, Zeynep Nurselin; Duzlu, Onder; Ozkilic, Gamze Nur; Inci, Abdullah; Pekmezci, Gokmen Zafer; Yildirim, Alparslan
Abstract: A total of 250 droppings of tumbler pigeons ( Columba livia domestica, Columbidae) were collected individually from different breeders in Turkey, to investigate the presence and genotyping of microsporidian species by nested PCR and to reveal their zoonotic potential. In the present study, Enterocytozoon bieneusi was the only microsporidian species identified in 35 pigeons with an overall molecular prevalence of 14.0%. Only one known genotype zoonotic Peru6 was identified in all positive samples according to the sequence analyses of the internal transcribed spacer region of ribosomal DNA of E. bieneusi . This study represents the first report of E. bieneusi in pigeons in Turkey. Our study also confirms the competence of breeding pigeons as hosts for the zoonotic Peru6 genotype, corroborating its potential role as a source of human infection and environmental contamination. Lay summary: Microsporidia are spore-producing fungi defined as emerging opportunistic pathogens of humans. The occurrence of microsporidia in animals could be risky for human public health. Home kept breeding pigeons pose a high risk for transmission of the microsporidians to humans.